Calculation of Optical Parameters of Thin Films of Structural Materials of Thermal Uncooled Bolometric Type Detector - Van Trieu Tran; K. V. Korsak; P. E. Novikov; I. Yu. Lovshenko; S. M. Zavadski; D. A. Golosov; A. A. Stepanov; A. A. Hubarevich; V. V. Kolos; Ya. A. Solovjov; D. S. Liauchuk; V. R. Stempitsky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The increased interest in utilizing uncooled thermal bolometer-type detectors (microbolometers) within the infrared or terahertz detection field is justified by their operational and technological characteristics, in particular: relatively low manufacturing cost, high detection efficiency, compatibility with silicon CMOS technology, and operation at room temperature. The performance of such detectors depends on optimizing critical parameters, which are dictated by both the geometrical design and the electrical, optical, and thermal properties of the materials used. The determination of optical parameters stands as a decisive factor in the design of microbolometer structures. This article delves into the examination of optical parameters of thin films of structural materials of microbolometer based on thermosensitive vanadium oxide film manufactured at JSC “INTEGRAL”. The investigation showcases the results of determining optical constants (refractive indexes n and absorption coefficients k) of thin films from the transmission curve by applying the reflection-transmission method. Furthermore, a comparison is carried out between the results of computer modeling of the transmission, reflection and absorption spectra – taking into account the obtained values of the coefficients n and k – and the empirical data from the in-situ experiment.